SOME ASPECTS OF THE THERMAL PROPERTIES OF SOLIDS - Bozorov Nosirzhon Sodikovich; Z. N. Yusupov; Umurkulov Kayumjon Parpievich; Alisherov Otabek Alisher coals; Zhaloliddinova Sarvigul Odiljon kizi (Galaxy International Interdisciplinary Research Journal, 2024)
The article outlines the main principles about the thermal movement of particles in crystals. Thermal expansion is caused by an increase in the energy of vibrating particles. The vibrations become anharmonic (non-harmonic). If, when heated, a solid body does not have the opportunity to expand freely, then very large stresses arise, which must be taken into account in practice.